PT Pupuk Kalimantan Timur’s Sustainability Strategy Becomes the Winner of ASRRAT 2024 - Bhayangkara, Ida Bagus Ketut; Bandiah, Andini Putri (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the sustainability strategy of PT Pupuk Kalimantan Timur (PKT) in the context of its success in winning the 2024 ASRRAT (Asia Sustainability Reporting Rating) award. Using a descriptive qualitative approach, this study explores the company’s commitment to environmental, social, and governance (ESG) aspects. Data were obtained through an in-depth review of sustainability reports and other secondary sources. The results of the analysis show that PKT implements various strategic sustainable initiatives, such as energy efficiency, carbon emission reduction, community empowerment-based CSR programs, and transparent and accountable corporate governance. PKT’s success in achieving a "Platinum" rating in the 2024 ASRRAT reflects the consistency and effectiveness of the sustainability strategy implemented. This study concludes that comprehensively integrated sustainability practices are a key factor in achieving superior sustainability performance.